2020
DOI: 10.4244/eij-d-19-00602
|View full text |Cite
|
Sign up to set email alerts
|

Stroke after transcatheter edge-to-edge mitral valve repair: a systematic review and meta-analysis

Abstract: Aims:The aim of this study was to assess the stroke rate after transcatheter mitral valve repair (TMVR) with the MitraClip, comparing it with surgical mitral valve repair (SMVR) and optimal medical treatment (OMT). Methods and results:In December 2018, we systematically searched PubMed, Embase and Cochrane Controlled Register of Trials for studies comparing TMVR with SMVR and/or OMT for the treatment of severe mitral regurgitation. Random-effects and cumulative meta-analysis was performed. Ten studies were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Despite the risk of paradox embolism through an iASD, a meta-analysis found no difference in stroke rates in patients after MC therapy compared to patients on optimal medical therapy. The postprocedural stroke rate tends to be decreased compared to surgical mitral therapy (p=0.19), which might be due to a higher incidence of de novo atrial fibrillation in surgical patients [ 48 •]. On the other hand, a diffusion MRI study reported an incidence of 86% new silent cerebral lesions after TEER in a cohort of 27 patients with a significant reduction in neurocognitive function tests if >3 cerebral lesions were present.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the risk of paradox embolism through an iASD, a meta-analysis found no difference in stroke rates in patients after MC therapy compared to patients on optimal medical therapy. The postprocedural stroke rate tends to be decreased compared to surgical mitral therapy (p=0.19), which might be due to a higher incidence of de novo atrial fibrillation in surgical patients [ 48 •]. On the other hand, a diffusion MRI study reported an incidence of 86% new silent cerebral lesions after TEER in a cohort of 27 patients with a significant reduction in neurocognitive function tests if >3 cerebral lesions were present.…”
Section: Complicationsmentioning
confidence: 99%
“…High rates (11.7%) of newly diagnosed AF were described at the Pilot European Sentinel Registry, whereas lower rates of 1.2% were found in the GRASP registry [ 23 , 53 ]. A meta-analysis of low cohort number studies showed an incidence of 2.4% of de novo AF after MC [ 48 •]. The clinical impact of de novo AF after TEER will have to be further investigated.…”
Section: Complicationsmentioning
confidence: 99%
“…Three of the included SRs were published in 2021 3,4,8 while 1 was published in 2020. 13 Each SR was based on relevant literature retrieved by systematic searches conducted in multiple databases (i.e., 2 or more) between December 2018 and June 2020. The number of primary studies included in the individual SRs ranged from 9 to 14.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The number of primary studies included in the individual SRs ranged from 9 to 14. In 1 SR of 12 studies, 13 which had a broader scope with an additional comparator of interest, 7 retrospective cohort studies were relevant to this report, while 5 were out of the scope. The 4 included SRs reported including 42 primary studies.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation